The ancestor of extant Japanese fancy mice contributed to the mosaic genomes of classical inbred strains - Takada, Toyoyuki; Ebata, Toshinobu; Noguchi, Hideki; Keane, Thomas M.; Adams, David J.; Narita, Takanori; Shin-I, Tadasu; Fujisawa, Hironori; Toyoda, Atsushi; Abe, Kuniya; Obata, Yuichi; Sakaki, Yoshiyuki; et al.

(untitled) (Genome Research, 2013)
Commonly used classical inbred mouse strains have mosaic genomes with sequences from different subspecific origins. Their genomes are derived predominantly from the Western European subspecies Mus musculus domesticus, with the remaining sequences derived mostly from the Japanese subspecies Mus musculus molossinus. However, it remains unknown how this intersubspecific genome introgression occurred during the establishment of classical inbred strains. In this study, we resequenced the genomes of two M. m. molossinus–derived inbred strains, MSM/Ms and JF1/Ms. MSM/Ms originated from Japanese wild mice, and the ancestry of JF1/Ms was originally found in Europe and then transferred to Japan. We compared the characteristics of these sequences to those of the C57BL/6J reference sequence and the recent data sets from the resequencing of 17 inbred strains in the Mouse Genome Project (MGP), and the results unequivocally show that genome introgression from M. m. molossinus into M. m. domesticus provided the primary framework for the mosaic genomes of classical inbred strains. Furthermore, the genomes of C57BL/6J and other classical inbred strains have long consecutive segments with extremely high similarity (>99.998%) to the JF1/Ms strain. In the early 20th century, Japanese waltzing mice with a morphological phenotype resembling that of JF1/Ms mice were often crossed with European fancy mice for early studies of “Mendelism,” which suggests that the ancestor of the extant JF1/Ms strain provided the origin of the M. m. molossinus genome in classical inbred strains and largely contributed to its intersubspecific genome diversity.